Infant- and Young Child-feeding Practices in Bankura District, West Bengal, India (Journal of Health, Population and Nutrition, 2010)
A community-based, cross-sectional descriptive study was conducted during June-July 2008 to assess theinfant- and young child-feeding (IYCF) practices in Bankura district, West Bengal, India. In total, 647 childrenaged less than two years selected through revised 40-cluster sampling using the indicators of theIntegrated Management of Neonatal and Childhood Illness (IMNCI) and World Health Organization. Theproportions of infants with early initiation of breastfeeding (13.6%) and exclusive breastfeeding under sixmonths (57.1%) and infants who received complementary feeding at the age of 6-8 months (55.7%) werelow. Appropriate feeding as per the IMNCI protocol was significantly less among infants aged 6-11 months(15.2%) and children aged 12-23 months (8.7%) compared to infants aged less than six months (57.1%),which could be attributable to low frequency and amount of complementary feeding. The main problemsrevealed from the study were late initiation of breastfeeding, low rates of exclusive breastfeeding, and inappropriatecomplementary feeding practices.Key words: Breastfeeding; Child-feeding practices; Cross-sectional studies; Descriptive studies; Exclusivebreastfeeding; Infant-feeding practices; IndiaDOI: 10.3329/jhpn.v28i3.5559J HEALTH POPUL NUTR 2010 Jun;28(3):294-299